A 5.0 Ghz Active Inductor Current Controlled Oscillator - Rajagopal, Chakaravarty D (2018)
The demand for wireless communications in the field of voice and data has rapidly grown. The integration level of Radio Frequency (RF) transceiver systems have become very intricate and efforts to deal with this has risen almost exponentially. Communications nowadays require system with extreme speeds to cater for high speed applications such as 4G and 5G, wider tuning range to cater for variety of applications, minimal timing errors and lower cost. Oscillators play the key role in determining the quality of the RF communications system. Most oscillators are voltage based and known as Voltage Controlled Oscillator (VCO) and comes mainly in two types, which are LC Tank Oscillators and Non LC-Tank Oscillators. The former is very good for lower phase noise due the usage of passive inductor. The latter such as ring oscillators are much smaller in size than LC-Tank, thus lower cost, but exhibit much higher phase noise. However, current sources are becoming more popular and employed in oscillator to form Current Controlled Oscillator (CCO) due to its higher frequency as compared to voltage source. Hence the goal has been put forth to design a CCO that produces 5 GHz center frequency, tuning range of 500 MHz and with phase noise better than -110 dBc/Hz by employing active inductor. To demonstrate the proposed concept, 5-stage ring oscillator with active inductor design controlled by a current-mode circuit, were designed and ran through simulation using 180 nm CMOS technology provided by Silterra. The work proceeds to validate and make improvements to the fundamental performance parameters of a local oscillator design that incorporates dual delay path, negative skewed delay, current source, cross-coupled transistors and active inductor. Analysis were done on how the cross-coupled transistors play a role in affecting the distinctive frequency operation pattern. Results from the simulation show that the oscillator’s maximum frequency obtained without distortion is 5.81 GHz. The cross coupled MOS transistors and active inductor controlled by current source aided well in improving the oscillator’s phase noise and frequency. Various simulation results show that the frequency range of this 5-stage oscillator runs between 3.87 GHz to 5.81 GHz. The critical parameter of any oscillator, which is the phase noise, is -113.2 dBc/Hz at 1 MHz offset with a center frequency of 5.81 GHz. The performance of this new design has improved, in general, about 36% on the frequency while 8% on the phase noise as compared with the non-LC Tank topology. Apart from the frequency and phase noise, the output power and size of this design is 9.41 dBm and 0.22 mm2 respectively. This is an improvement of 53% on the output power and 33% on the size when comparing with the non-LC Tank topology. Conclusively this design has successfully achieved the goals set forth for this research.